Nucleotide sequence and characterization of the transcript of a Dictyostelium ribosomal protein gene. - Steel, L F (1987)
Dictyostelium ribosomal protein mRNAs are subject to developmental regulation of both their translation and their stability. In order to consider whether such post-transcriptional regulation can be attributed to structural features of the mRNAs, we have cloned and sequenced a 1.9 kb EcoRI genomic DNA fragment which contains the gene for the Dictyostelium ribosomal protein 1024 (rp1024). The rp1024 gene contains a single intron of 350 bp which begins just after the fourth codon of protein coding sequence. Transcription begins 11 to 28 bp upstream from the initiator ATG in a pyrimidine rich region which is preceded by an oligo(dT)10 stretch, but which lacks a TATA box in the expected position. Processing of the 3' end occurs at either of two sites, resulting in two types of transcript which are present in equimolar amounts in both vegetatively growing and developing cells. Therefore, their relative abundance shows no correlation with the changes in translatability and stability of r-protein mRNAs which occur during development. A comparison of the sequence of the 5'-untranslated region of rp1024 mRNA to those of other Dictyostelium mRNAs shows that it differs significantly, primarily in its relatively high G+C content.